Features of the educational process in Ukraine in modern conditions (problems, comparisons, prospects) - Garmash, Sergii (My University, 2022)
The aim of the work is to highlight changes in the educational process of Ukraine, which is an integrated component of the overall process of fleeting negative changes in the country as a whole in modern conditions. Today, the redistribution of spheres of influence between the world leaders at the expense of the interests of third countries has become a negative trend in the twenty-first century. Distance learning becomes relevant during the hostilities of the full-scale war that is going on in Ukraine. On the basis of causal relations, it is proposed to investigate the purposeful destructive «reforming» of the education system itself, which aims not so much to reduce the cost of its operation and gradual decline, but as to instill in young people «clip thinking» far from critical thinking. (It is very convenient to manipulate such consciousness in one's own interests). It has been proven that in recent years distance learning has been presented and introduced more and more persistently, and the bureaucracy of science is gaining momentum with its artificial «achievements», which are only declarative in nature. It is concluded that: 1) «gadgetization» of life and lack of socialization in distance learning are the biggest shortcomings that can further affect the development of man himself and the development of the society as a whole; 2) there is a threat of further social stratification of society, increasing the gap between opportunities in different social groups; 3) distance learning in the current circumstances of hostilities and the imposition of martial law on the territory of Ukraine is an appropriate form of education in the country for a short period.
Keywords: educational process; distance learning; gadgetization of life; clip thinking; destructive reforming; martial law; social stratification of society